Ayurveda’s Approach to Avascular Necrosis: A Case Study - Negi, Shalini; Padavi, Dnyaneshwar M (International Research Journal of Ayurveda & Yoga, 2023)
Avascular necrosis (AVN) is also known by various other terms such as osteonecrosis, bone necrosis, bone infarction, aseptic necrosis, and ischemic necrosis. AVN is a medical condition that occurs when there is a disruption of blood supply to a specific area of bone tissue, resulting in the death of bone cells. This condition can be correlated to Asthi- Majjagata Vata according to the sign and symptoms described in Ayurveda. Aims and Objectives: The aim of the study was to assess the efficacy of tiktaka kshira basti, Jaloka Avacharan (leech therapy) and Shastikashali Pinda Swedana with oral Ayurveda medicine in the management of AVN. The objective was to reduce the need of surgical intervention. Materials and Methods: A diagnosed and non-operated case of AVN of hip joint with complaints of pain of bilateral hip joint and restricted movements was managed by Ayurvedic approach. Observation and Results: Significant improvement was noticed after the treatment. Pain was reduced significantly with improvement in the range of movement.